Pelaksanaan Pidana Kebiri Kimia; Disparitas antara Kode Etik Kedokteran dengan Perintah Undang-Undang - Aguk Nugroho; Nur Aziz; Muhammad Fikri Jauhari; Daryuti (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study aims to analyze the implementation of chemical castration as well as the conflict between the medical code of ethics and statutory mandates. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that the implementation of chemical castration has been comprehensively regulated under Government Regulation No. 70 of 2020, including the stages of assessment and execution, and is juridically mandated to be carried out by medical personnel. The Medical Code of Ethics cannot serve as a basis for refusal, as it is subordinate to positive law (lex superior derogat legi inferiori).It is recommended that regulatory harmonization and more operational technical guidelines be developed for medical personnel.